2022
DOI: 10.1021/acs.jpcc.2c05694
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Multiple Island Layers during Iron Oxide Atomic Layer Deposition: An Electron Microscopy and Spectroscopic Ellipsometry Investigation

Abstract: Atomic layer deposition (ALD) of FeOx thin films, prepared using the air stable and low cost precursor of ethylferrocene, was characterized through electron microscopy and spectroscopic ellipsometry (SE) techniques. To model the growth behavior of the layer on carbon-based air electrodes in metal–air batteries, carbon substrates were employed for electron microscopy. Electron imaging revealed an island morphology for the FeOx deposits, which eventually coalesced into a continuous film with pinholes. Further gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Aggressive deposition techniques, such as those involving high temperatures or oxidizing chemicals, can damage carbon-based GDLs and hydrophobic agents (e.g. PTFE) [17,67]. The use of non-carbon GDLs and ex-situ hydrophobic treatments is a potential workaround to these limitations.…”
Section: Direct Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Aggressive deposition techniques, such as those involving high temperatures or oxidizing chemicals, can damage carbon-based GDLs and hydrophobic agents (e.g. PTFE) [17,67]. The use of non-carbon GDLs and ex-situ hydrophobic treatments is a potential workaround to these limitations.…”
Section: Direct Methodsmentioning
confidence: 99%
“…To overcome this, a protective sublayer of ALD MnO x was deposited prior to FeO x ALD [85]. The MnO x sublayer also enhanced the growth characteristics of the FeO x process and it was found that the FeOx ALD process experienced multiple stages of island growth, a phenomenon not typical in ALD [67]. By mixing the ORR-active MnO x ALD layer developed by Clark et al [84] with the OER-active FeO x ALD layer, a bifunctional catalyst was developed via direct ALD.…”
Section: Direct Methodsmentioning
confidence: 99%
See 3 more Smart Citations